ASTRONOMI ISLAM DAN TEORI HELIOCENTRIS NICOLAUS COPERNICUS - Hambali, Slamet (Al-Ahkam, 2013)
In the 13th century BC Heliocentric concept presented by the Greek philosopher: Aristarchus. But the theory is still a hypothesis, and contrary to the opinion of Aristoteles. Heliocentric theory has not been able to replace Geocentric one, especially with the emergence of Ptolemy (140 AD), known as a pioneer of the Geocentric theory, who wrote a big book titled Almagest which astronomers have refered for centuries. But after Nicolaus Copernicus wrote a book with the title De Revolutionibus Orbium Coelestium, his published heliocentric theory, and finally It was able to undermine Geocentric theory that has long been established. Qur'an which was revealed long ago before this theory has been presented, has explained the astronomical concept such us motion of earth, that aligned with the Heliocentric theory. In the Qur'an there are some verses of earth, moon and sun, among others: Surat YÅ«nus: 5, al-Naml: 88, YÄsÄ«n: 38, dan 40, al-AnbiyÄâ€™: 33, Ä€li â€˜ImrÄn: 190. According to the exegete such Aá¸¥mad Musá¹afÄ al-MarÄghÄ« in his book Tafsir al-MarÄghÄ«, that the Heliocentric theory was the one that inline with the Qur'an,and that the Heliocentric theory is a part of the miracle of the Qur'an.